Ponzi Schemes in the Caribbean - Carvajal, Ana (IMF Working Papers; Working Paper ;, 2009)
In several Caribbean states, unregulated investment schemes grew quickly in recent years by claiming unusually high monthly returns and through a system of referrals by existing members. These are features shared with traditional Ponzi schemes and pyramid schemes. This paper describes the growth of such schemes, their subsequent collapse, and the policy response of regulators, and presents key policy lessons. The analysis and recommendations draw on country experiences in the Caribbean, and in such diverse countries as the United States, Colombia, Lesotho, and Albania.